Development Of A Flipbook-Based E-Module For Pancasila Education To Improve Learning Outcomes Of Grade Iv Students At Sd Swasta Kartini Medan Area - Rahman, Anisa; Yunita, Sri; Lubis, Wildansyah; Bungana, Reh; Saragi, Daulat; Winara, Winara (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to develop a flipbook-based e-module for Pancasila Education that is valid, practical, and effective in improving learning outcomes for Grade IV students at SD Swasta Kartini. This research applies the Research and Development (RD) method using the 4D development model. The research results show: (1) Validity was determined through expert validation. Subject matter experts gave a score of 83% (Valid with revisions) in the first stage and 88% (Highly Valid) in the second. Media experts scored 65% (Fair with revisions) initially and 93% (Highly Valid) after revision. Language experts gave 83% (Fair with revisions) at first and 96% (Highly Valid) after improvements. (2) Practicality was assessed through questionnaires distributed to teachers and students. The teachers’ practicality score was 95% (Highly Practical), while students’ responses reached 87% (Highly Practical). (3) Effectiveness was measured using the n-gain test, with a result of 0.71 (Very High), indicating a significant improvement in student learning outcomes. The conclusion is that the developed flipbook-based e-module for Pancasila Education is valid, practical, and effective in enhancing students’ learning achievements in the subject of Pancasila Education.